Lessons from private equity any company can use - Gadiesh, Orit.; MacArthur, Hugh. (Boston, Mass. : Harvard Business School Press, 2008)
Gadiesh and MacArthur use the concise, actionable format of a memo to lay out the five disciplines that private equity firms use to attain their edge. This could be your opportunity to build the results-driven culture that will put your firm on par with private equity.
Introducing the private equity advantage -- What is going on in private equity? -- How can PE lessons applyu to you? -- Define the full potential -- Develop the blueprint -- Accelerate performance -- Harness the talent -- Make equity sweat -- Foster a results-oriented mindset -- Conclusions -- Lessons.
Description based on print version record.
Keywords: Private equity; Venture capital; Investments; Investments; Private equity; Venture capital; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books